Computed tomography imaging‐based observation of the aggressive growth of angiosarcoma: a case study. Issue 8 (26th August 2019) - Kubo, Sousuke; Kobayashi, Nobuaki; Kaneko, Ayami; Aiko, Hiroko; Kudo, Makoto; Kaneko, Takeshi
Abstract : An 82‐year‐old man with chronic tuberculous empyema visited our hospital for an annual computed tomography (CT) scan. No differences were noted between the CT scan at presentation and a scan performed a year previously in August 2017. He began experiencing right chest, epigastrium, and back pain since the end of October 2017. A CT scan taken in November of 2017 to evaluate the pain in his right chest, epigastrium, and back showed an irregular thickening of the pleura adjacent to the empyema and an abnormal right seventh costal mass infiltrating the vertebral body. CT‐guided needle biopsy of the mass showed angiosarcoma. Positron emission tomography/CT revealed multiple metastases in his bones and liver. Chemotherapy was not recommended owing to his poor performance status, which was related to angiosarcoma. Therefore, he was offered palliative radiotherapy for the metastasis to the vertebral body. Abstract : Here, we report a case of pyothorax‐associated angiosarcoma. Our patient had computed tomography (CT) scans of the chest annually to monitor chronic empyema, and to screen for cancers. Our patient was diagnosed with angiosarcoma within a month period after complaining of chest pain. This is the very first report on angiosarcoma whose aggressive growth could be observed on CT imaging.